Diagnosis of the Origin of Acute Otitis and Modern Clinical Diagnostic Methods - Yoqub oʻgʻli, Mardonov Umarjon; J. A, Khatamov (Journal of Science in Medicine and Life, 2025)
The etiology of acute otitis media can be viral or bacterial. As a rule, the viral course of the disease is complicated by the addition of bacterial inflammation. In newborns, gram-negative bacilli of the small intestine, especially Escherichia coli and Staphylococcus aureus, cause acute otitis media. In older infants and children under 14 years of age, the most common pathogens are Streptococcus pneumoniae, Moraxella (Branhamella) catarrhalis, and non-typeable strains of Haemophilus influenzae; less common pathogens are group A beta-hemolytic streptococci and S. aureus. For patients older than 14 years of age, S. pneumoniae, group A beta-hemolytic streptococci and S. aureus, followed by H. influenzae.